Digital Governance in the Management of Local Revenue in the City of Makassar - Muhammad Fuad Arfandi; Muh. Akmal Ibrahim; Hasniati Hasniati; Didik Iskandar (Journal Social Civilecial, 2025)
Advances in information and communication technology have driven significant changes in public administration, including the management of Local Own-Source Revenue (PAD). The Makassar City Government, through the Regional Revenue Agency (Bapenda), has developed various digital-based local tax services such as the PAKINTA application, cashless payments via QRIS and Virtual Accounts, and an integrated electronic tax service system. This study aims to analyse Digital Governance in the management of Makassar City’s Local Own-Source Revenue based on a Digital Governance approach encompassing control, coordination, incentives, and trust. This study employs a qualitative approach. Data collection was conducted through observation, interviews, and documentary analysis. Key informants included the Regional Revenue Agency (Bapenda) and other government agencies, taxpayers, banks, and third parties (digital innovation developers). Data analysis involved the stages of data reduction, data presentation and drawing conclusions. The research results indicate that the implementation of Digital Governance in the management of the City of Makassar’s Local Revenue has established a more integrated local tax payment system through the use of cashless transactions, the integration of electronic payments, digital communication between institutions, and real-time monitoring of local revenue. Digital PAD management in Makassar City demonstrates a shift from manual service delivery towards an electronic-based local revenue management system involving inter-agency coordination, supervision of digital transactions, and the use of various electronic payment channels in local tax services. It can be concluded that Digital Governance in the management of Makassar City’s PAD has established a more integrated electronic payment-based local revenue management system compared to the previous manual service delivery model.